What can Beijing learn from the world megacities on energy and environmental issues? - Xinxin Zhang; Zhenggang Lu; Maogang He; Jingfu Wang (Energy Reports, 2022)
In order to build Beijing into a world-class harmonious and livable capital city, its energy and environmental issues deserve special attention. Considering London’s experience and achievements in tackling smog crisis, New York’s world-class city positioning and influence, and Tokyo’s geographical and cultural characteristics, these three world-class megacities are taken as examples in this study for investigating and analyzing the establishment and optimization of an urban energy system which is clean, efficient, safe, and sustainable. The urban planning strategies, planning experience, and related energy policy of these three megacities for building low-carbon cities are reviewed and their enlightenment to Beijing is discussed. The study of international cases has a certain reference effect on the energy structure adjustment and urban planning practices related to Beijing’s construction of a low-carbon city.